EFEKTIVITAS KOMUNIKASI TELEPON SELULER PENJUALAN TOMAT KECAMATAN PANGALENGAN KABUPATEN BANDUNG - Endang Sulastri, Gontom Kifli, Budi Guntoro, dan (Sekolah Pascasarjana UGM, 2015)
The access to information on the selling price of tomatoes by tomato growers is perceived very limitedin the pastin Pangalengan District. The appearance of information technology, such as mobile phone,provides opportunities for tomatoes growers to obtain the access to more information, wider, fasterand cheaper. The general objective of this research is to identify the behavior of tomato growersâcommunication and the influence aspects of the use of mobile phones toward the effectiveness ofcommunication in Pangalengan District. The method for this research is explanatory survey research.Two-steps random sampling has been used in this research with selected sample of 165 respondents.The research unit is focused on the tomatoes growers who used mobile phones. The result indicates thatthe tomato growers in Pangalengan District perceive the use of mobile phones provides benefits to havemore options for the selling price of tomatoes. The result of statistical analysis shows that the use ofmobile phones among tomato growers and tomato sellers has given significant effect on the effectivenessof communication and increasing the intensity of tomato sales.From this research, it is recommendedto provide the information management of the selling price of tomatoes via mobile phones involvingAgriculture Information Officer (PIP) which already exist today.